The impact of belonging to a women network in STEM: A Latin American sorority network - Lara-Prieto, Vianney; Peralta, María Haydée; Barrios-Martínez, Janny Alexandra; Páez-Pino, Adriana; Larrondo-Petrie, Maria M.; Ruiz-Cantisani, M. Ileana (LACCEI, 2023)
Addressing the gender gap in STEM fields remains a global challenge that resonates throughout affects society. To effectively narrow this gap and increase female representation in Engineering and Sciences, a multifaceted approach involving educational institutions, companies, government bodies, and society at large is imperative. This work presents some of the initiatives carried out over the course of a year by the Matilda Latin American Open Chair for Women in Engineering, a group of persons advocating for the empowerment of women in STEM disciplines. The Chair ́s mission is rooted in increasing the visibility of women in Engineering and Sciences, inspiring new vocations, and retaining and developing those women who are pursuing a career in STEM. Implementing a mixed methods approach, this study highlights the impact of these actions on both the broader public and the personal and professional lives of its members. Notable initiatives that have reached a substantial audience include the Matilda book series, enlightening talks and conferences, the research symposium, and the WhatsApp group facilitating communication among Matilda Chair members. Regarding the impact of participating in these initiatives, most members mention the value of collaborating with other people in Latin America who share a common commitment to advancing gender equality in STEM. The spirit of camaraderie has fostered a sense of community and sorority within the network, and a collective dedication to inspiring more women to see engineering as a viable and fulfilling professional and life pathway.